Fuzzy Retractions of Fuzzy Open Flat Robertson-Walker Space - A. E. El-Ahmady; A. S. Al-Luhaybi (Advances in Fuzzy Systems)
Our aim in the present paper is to introduce and study new types of fuzzy retractions of fuzzy open flat Robertson-Walker model. New types of the fuzzy deformation retracts of model are obtained. The relations between the fuzzy foldings and the fuzzy deformation retracts of model are deduced. Types of fuzzy minimal retractions are also presented. New types of homotopy maps are deduced. New types of conditional fuzzy folding are presented. Some commutative diagrams are obtained.